TEMPERATURE PATTERNS DURING THE ORGANIC ORGANIC WASTE ORDERS OF NATURAL CHILDREN IN NATURAL ENVIRONMENT AND ARTIFICIAL ENVIRONMENT - H Yulipriyanto (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2005)
The purposes of this work are (I) to determine the pattern of temperature during the composting of organic waste of chicken manure at the natural and artificial environment (2) to determine the chemical characteristics of chicken manure Around 700 kg organic wastes of chicken manure put in the hole of land with 2 m length, x2m wide x lm height. The other organic waste in same size put in the artificial environment. During the composting we turn the heap of compost every two weeks especially for organic waste that composted in artificial environment. The data we want to collect is the temperature of the heap of compost in the exterior zone (0-20 em, ), deep zone (50 cmfrom surface,) and low zone (80 cm,from surface). We also analyse the chemical characteristics include the pH, N,P,K total, NH4, Ca .Mg total and c/N ratio; while the organic fraction analysis include the cellulose, lignin, protein, total sugar. The pattern of temperature during composting present the thermophilic phase in the beginning of composting for organic wastes of chicken manure that composted in artificial condition. But this thermophilic phase only rest for one week While natural environment give the thermophilic phase longer until more than 4 weeks. Based on this results we can conclude that the rate of organic waste of chicken manure decomposition during the composting in artificial environment is more quick than that in the natural environment. The chemical characteristics of chicken manure composted show the high contain of NH4, but in the artificial condition the looses of water is higher. Based on the results of organic fraction, the biodegradation of cellulose and lignin in the natural environment is significant than that in the artificial condition.